Duolingo Application as Media in Teaching Vocabulary Mastery - Imam nur Aziz; Mariana Ulfah Hoesny (JEET, Journal of English Education and Technology, 2023)
This study aims to see how the Duolingo application affects students' vocabulary competence in the seventh grade in junior high school. Vocabulary is crucial for pupils to acquire since it helps them communicate. A quasi-experimental design was adopted, with 20 students as the experimental group and 20 as the control group. The result demonstrates that at the 5% significance level, to= 2.881 is greater than tta= 1.672. It suggests that utilizing the Duolingo program might improve pupils' vocabulary proficiency. Ho was refused but Ha was accepted.